The idea of America : reflections on the birth of the United States - Wood, Gordon S. (New York : Penguin Press, 2011)
A Pulitzer Prize-winning historian of the American Revolution explains why it remains the most significant event in our history. In a series of elegant and illuminating essays, Wood explores the ideological origins of the revolution--from ancient Rome to the European Enlightenment--and the founders' attempts to forge an American democracy.
Rhetoric and reality in the American Revolution -- The legacy of Rome in the American Revolution -- Conspiracy and the paranoid style -- Interests and disinterestedness in the making of the Constitution -- The origins of American Constitutionalism -- The making of American democracy -- The radicalism of Thomas Jefferson and Thomas Paine considered -- Monarchism and republicanism in early America -- Illusions of power in the awkward era of federalism -- The American enlightenment -- A history of rights in early America -- Conclusion : the American revolutionary tradition, or why America wants to spread democracy around the world.
Includes bibliographical references and index.
Keywords: United States; Democracy -- United States; Republicanism -- United States; United States -- History -- Revolution, 1775-1783 -- Influence; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.